2009
DOI: 10.2164/jandrol.108.006494
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aggressiveness of Human Prostate PC‐3 Tumor Cells Expressing Cell Surface Localized Membrane Type‐1 Matrix Metalloproteinase (MT1‐MMP)

Abstract: Membrane type-1 matrix metalloproteinase (MT1-MMP) is a multidomain transmembrane endopeptidase with a major role in physiological and pathological processes through proteolysis of extracellular matrix and other pericellular proteins. We examined cell surface function of MT1-MMP in PC-3 human prostate tumor cells selected for metastasis in nude mice (PC-3-LN4), or transfected with the full-length wild-type (WT) MT1-MMP or with the mutant form lacking the cytoplasmic tail (DC-MT1-MMP). Enhanced cell surface MT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
5
21
0
Order By: Relevance
“…It has been shown that MT1-MMP resides in lipid rafts (38,39) and increased localization of MT1-MMP in lipid rafts enhances invasion of prostate cancer cells (40). Consistent with these reports, the present study found that MT1-MMP is preferentially localized in lipid raft fractions among major invadopodia components.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that MT1-MMP resides in lipid rafts (38,39) and increased localization of MT1-MMP in lipid rafts enhances invasion of prostate cancer cells (40). Consistent with these reports, the present study found that MT1-MMP is preferentially localized in lipid raft fractions among major invadopodia components.…”
Section: Discussionsupporting
confidence: 91%
“…This cleavage was shown to decrease cell adhesion to purified Ln-10, and to increase transmigration of DU-145 cells through cleaved Ln-10 and thus the basal lamina. Increased invasion mediated by MT1-MMP was also observed by Wang et al [34] . Using cells engineered to overexpress MT1-MMP (namely PC3-LN4), invasion into type-I collagen gels in vitro was observed, through activation of pro-MMP2.…”
Section: Functions Of Mt-mmps In Prostate Cancer Progression and Metasupporting
confidence: 64%
“…MMP-14 differs from other MMPs as it is membrane bound through a transmembrane domain with its catalytic center on the outside of the cell [64] . Its expression in prostate cancer cells is associated with androgen independence [65] and aggressiveness [66] . Prostate tumors primarily metastasize to bone, and MMP-14 has a particularly important role in this process due to HOX transcription factors regulate genes in prostate cancer cells that modify the tumor microenvironment, as well genes in stromal cells that support tumor growth.…”
Section: Hox Transcription Factors and Metastasismentioning
confidence: 99%